Evolution and taxonomy in capitate hydroids and medusae (Cnidaria: Hydrozoa) - Petersen, K. W. (Zool. Journ. Linn. Soc, 1990)
A cladistic analysis of Capitata groups the families in four suborders based on medusa characters (such as manubrium morphology, position of gonads, and position and number of marginal tentacles) and hydroid characters (such as presence or absence of an oral tentacle whorl, and the different development of the tentacles of the oral and aboral whorls). On the family and generic levels, the revision results in changes which unite the separate hydroid and medusa taxonomic systems, defining genera which are not based on characters solely relating to the reduction of medusae to fixed gonophores. In those families where the reduction of the medusa can be analysed, it is shown that the reduction occcurred after all synapomorphies defining the genera had evolved and usually affected individual species within a genus rather than the original species from which the other species in the genus evolved. This supports the view that medusa reduction is not in itself a valid generic character. A discussion of the theories of 'inconsistent' or 'mosaic' evolution concludes that no difference in evolutionary rate or degree of specialization can be demonstrated among taxa with free medusae and taxa with gonophores. figs. 1-49. Descriptors: Ectopleura americana, Ectopleura indica, Ectopleura mayeri, Ralpharia gorgoniae, Ralpharia neira, Tubularia acadiae, Zyzzyzus calderi, Zyzzyzus floridanus, Zyzzyzus robustus